Tisagenlecleucel in adult relapsed or refractory follicular lymphoma: the phase 2 ELARA trial - Fowler, Nathan Hale; Dickinson, Michael; Dreyling, Martin; Martinez-Lopez, Joaquin; Kolstad, Arne; Butler, Jason; Ghosh, Monalisa; Popplewell, Leslie; Chavez, Julio C.; Bachy, Emmanuel; Kato, Koji; Harigae, Hideo; et al. (Nature Medicine, 2022)
Tisagenlecleucel is an autologous anti-CD19 chimeric antigen receptor-T cell therapy with clinically meaningful outcomes demonstrated in patients with relapsed/refractory (r/r) B-cell lymphoma. In a previous pilot study of tisagenlecleucel in r/r follicular lymphoma (FL), 71% of patients achieved a complete response (CR). Here we report the primary, prespecified interim analysis of the ELARA phase 2 multinational trial of tisagenlecleucel in adults with r/r FL after two or more treatment lines or who relapsed after autologous stem cell transplant (no. NCT03568461). The primary endpoint was CR rate (CRR). Secondary endpoints included overall response rate (ORR), duration of response, progression-free survival, overall survival, pharmacokinetics and safety. As of 29 March 2021, 97/98 enrolled patients received tisagenlecleucel (median follow-up, 16.59 months; interquartile range, 13.8–20.21). The primary endpoint was met. In the efficacy set ( n = 94), CRR was 69.1% (95% confidence interval, 58.8–78.3) and ORR 86.2% (95% confidence interval, 77.5–92.4). Within 8 weeks of infusion, rates of cytokine release syndrome were 48.5% (grade ≥3, 0%), neurological events 37.1% (grade ≥3, 3%) and immune effector cell-associated neurotoxicity syndrome (ICANS) 4.1% (grade ≥3, 1%) in the safety set ( n = 97), with no treatment-related deaths. Tisagenlecleucel is safe and effective in extensively pretreated r/r FL, including in high-risk patients. In a prespecified interim analysis of a pivotal phase 2 trial, tisagenlecleucel, an autologous CD19-targeting CAR-T cell therapy, produced a high rate of complete responses with a manageable safety profile in adults with relapsed or refractory follicular lymphoma